In vitro propagation of Leucocroton havanensis Borhidi (Euphorbiaceae): A rare serpentine-endemic species of Cuba. (4th July 2018) - Alfonso, Dubiel; Cicatelli, Angela; Guarino, Francesco; Rodríguez, Daymara; Castiglione, Stefano
Abstract: Leucocroton havanensis Borhidi is an endemic plant species of Cuba able to hyperaccumulate nickel. In order to sustain the conservation of this species, an efficient protocol for its micropropagation, via axillary bud proliferation, is described. We placed apical segments from aseptic seedlings on basal medium supplemented with indole-3-acetic acid (IAA) and 6-benzylaminopurine (BAP) or thidiazuron (TDZ), individually or in combination. On a medium containing 0.5 mg L −1 IAA and 1.0 mg L −1 BAP explants (65.5%) developed axillary buds. Nevertheless, combinations of 0.5 mg L −1 IAA with 0.1 mg L −1 TDZ was the most effective treatment producing the highest number of buds per explant (30.3); while the control treatment, without growth regulators, produced no buds at all. Transfer of buds to medium supplemented with indole-3-butyric acid, indicated that 0.25 mg L −1 is the amount of hormone required to generate roots on young buds (100%). In order to assess DNA variations in micropropagated plants, an Amplified Fragment Length Polymorphism analysis was performed and no genetic variation was detected. This study demonstrates that a high multiplication rate can be obtained by means of the reported protocol, and that plantlets can be readily hardened (96% survival) in a greenhouse by transplanting them on serpentine soil.